‘Safeguarding moral decency’: A Queer discourse analysis of Russian president Vladimir Putin’s sexualized discourses and boundary-making in the Russian-Ukraine war - Rasmusson,Johanna (2023)
The thesis investigates discourses on sexual orientation, gender identity, and expression in national addresses performed by Russian President Vladimir Putin since the large-scale invasion of Ukraine in February 2022. It applies an embedded approach of Critical Discourse Analysis and Queer Linguistics to disseminate how such discourses are produced by Putin in the war. The theoretical approach of Nira Yuval Davis (2011) ‘politics of belonging’ is employed to analyze in which ways such discourses are instrumentalized in a political effort to construct a Russian national community of belonging and its performative function in the war. The analysis identifies how the discourses naturalize heteronormativity and gender binarism as well as antagonize non-heteronormative gender identities and sexualities by the invocation of cultural, moral, religious, and anti-Western values. The analysis further demonstrates the construction of a national community of belonging which produces a threatening sexualized ‘Other’ that poses an acute threat to the Russian nation. Finally, it concludes that Putin’s demonization of non-heteronormative subjects carries an important function in the war by providing a legitimizing and mobilizational foundation.
Keywords: Putin; discourse; gender identity; sexuality; national belonging